2011
DOI: 10.1093/icesjms/fsr156
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between fish stock changes in the Baltic Sea and the M74 syndrome, a reproductive disorder of Atlantic salmon (Salmo salar)

Abstract: Mikkonen, J., Keinänen, M., Casini, M., Pönni, J., and Vuorinen, P. J. 2011. Relationships between fish stock changes in the Baltic Sea and the M74 syndrome, a reproductive disorder of Atlantic salmon (Salmo salar). – ICES Journal of Marine Science, 68: 2134–2144. The M74 syndrome of Baltic salmon (Salmo salar), which appears as increased yolk-sac fry mortality (YSFM), impairs the reproduction of salmon stocks. Changes in the prey stocks of Baltic salmon in its two feeding areas, the southern Baltic Proper (BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
110
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(129 citation statements)
references
References 18 publications
3
110
1
Order By: Relevance
“…Moreover, Pickova et al [15] found an imbalance between the oxidative potential and antioxidant capacity in the eggs of salmon whose offspring suffered from M74. The M74 syndrome has been linked to a large food biomass and an abundance of sprat (Sprattus sprattus) in the Baltic Proper (BPr) [16,17]. According to Keinänen et al [18], a high lipid content in the prey fish biomass of salmon and an abundant supply of lipid-rich food explains the incidence of thiamine deficiency.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, Pickova et al [15] found an imbalance between the oxidative potential and antioxidant capacity in the eggs of salmon whose offspring suffered from M74. The M74 syndrome has been linked to a large food biomass and an abundance of sprat (Sprattus sprattus) in the Baltic Proper (BPr) [16,17]. According to Keinänen et al [18], a high lipid content in the prey fish biomass of salmon and an abundant supply of lipid-rich food explains the incidence of thiamine deficiency.…”
mentioning
confidence: 99%
“…There, the proportions of sprat and herring have mainly varied as a consequence of large changes in the size of the sprat stock. Sprat has been the most prevalent species in the BPr since the end of the 1980s, i.e., after the collapse of the stock of cod (Gadus morhua), which is its main predator [17,24].…”
mentioning
confidence: 99%
See 3 more Smart Citations